2004
DOI: 10.1016/j.ejvs.2003.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Endotension is Influenced by Wall Compliance in a Latex Aneurysm Model

Abstract: This in vitro model demonstrated that the aneurysm sac mean pressure (ASPmean) and the aneurysm sac pulse pressure (ASPpulse) were significantly influenced by the compliance of the aneurysm wall. These data highlight the need for further studies regarding endotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…8 that the influence of EVG wall compliance on possible migration appears to be insignificant. Specifically, when the EVG wall compliance increases from 1.8 to 7.8% per 100 mmHg of blood pressure change, the migration force only decreases by 0.2 N. However, one cannot say that EVGwall compliance is not important because the degree of EVGwall compliance determines the sac pressure and hence the AAA wall-stress as a result of the fluid-structure interaction effects (Gawenda et al 2004;Li 2005).…”
Section: Factors Effecting Migration Force On Evgmentioning
confidence: 97%
See 2 more Smart Citations
“…8 that the influence of EVG wall compliance on possible migration appears to be insignificant. Specifically, when the EVG wall compliance increases from 1.8 to 7.8% per 100 mmHg of blood pressure change, the migration force only decreases by 0.2 N. However, one cannot say that EVGwall compliance is not important because the degree of EVGwall compliance determines the sac pressure and hence the AAA wall-stress as a result of the fluid-structure interaction effects (Gawenda et al 2004;Li 2005).…”
Section: Factors Effecting Migration Force On Evgmentioning
confidence: 97%
“…Particularly, our simulation results indicated that even in the absence of any kind of endoleaks the sac pressure can be generated by the complex fluid-structure interactions between luminal blood flow, EVG wall, stagnant sac blood, and aneurysm wall. Gawenda et al (2003); Gawenda et al (2004) measured the sac pressure with in vitro stented aneurysm models under the conditions of non-endoleaks and found that, indeed, the sac pressure is determined by the EVG/AAA wall compliance.…”
Section: Impact Of Evg Presencementioning
confidence: 99%
See 1 more Smart Citation
“…The aneurysm sac pressurei sr educed when the aneurysm is successfully excluded (20) and at least in the experimental situation, the ePTFE graft reduces the intra-aneurysm sac pressurem oret han the Dacron graft (21) does. however,due to several other factors influencing the pressure, such as aneurysm sac volume, patent side branches, wall compliance and the systemic blood pressure ( 22,23), the importance in theclinicalsituation is not yet defined. The aorto-uniiliac system, though, leads to al ower sac pressure than the aortobi-iliac systems.…”
Section: Prostethic Materialsmentioning
confidence: 99%
“…26 Gawenda et al performed an in vitro experiment with latex aneurysm models of variable compliance. 27 After endovascularly excluding the aneurysm sac and measuring the circumferential compliance, as well as the sac's mean and pulse pressure relative to the systemic mean pressure, they concluded that the intrasac pressure was influenced inversely by the compliance of the aneurysm wall; a decrease in compliance resulted in an increase of the pressure parameters, showing that stiffer AAAs are associated with higher intrasac pressures, 27 which in turn can influence the sac shrinkage process. The implantation of a stent-graft has been associated with a decrease in the AAA compliance.…”
Section: Remodeling Of the Aneurysm Wallmentioning
confidence: 99%